Global trends in research on oxidative stress associated with periodontitis from 1987 to 2022: A bibliometric analysis - Xin, Xirui; Xiang, Xingchen; Xin, Yu; Li, Qiong; Ma, Haonan; Liu, Xinchan; Hou, Yubo; Yu, Weixian (Frontiers in Immunology, 2022)
Background: Oxidative stress has been implicated in many chronic inflammatory diseases, including periodontitis. To date, however, only a few bibliometric analyses have systematically studied this field. This work sought to visualize research hot spots and trends in oxidative stress associated with periodontitis from 1987 to 2022 through bibliometric approaches. Methods: The Web of Science Core Collection was searched to retrieve relevant publications. HistCite, VOSviewer, and CiteSpace were used to perform bibliometric analysis visually in terms of annual output, active countries, prolific institutions, authors, core journals, co-cited references, and co-occurrence of keywords. Results: A total of 1654 documents were selected for analysis. From 1 January 1987 to 11 June 2022, the number of annual publications related to oxidative stress in periodontitis exhibited an upward trend. The most prolific country was China with 322 documents, but the United States had 11334 citations. Okayama University, University of Birmingham, and Sichuan University were the most active and contributive institutions. The Journal of Periodontology ranked first in terms of numbers of publications and citations. Ekuni was the most prolific author, while Chapple ranked first among co-cited authors. The Role of Reactive Oxygen and Antioxidant Species in Periodontal Tissue Destruction published by Chapple was the most frequently co-cited reference. Keyword co-occurrence showed that oxidative stress was closely related to inflammation, antioxidants, and diabetes. Conclusion: Our research found that global publications regarding research on oxidative stress associated with periodontitis increased dramatically and were expected to continue increasing. Inflammation and oxidative stress, and the relationship between periodontitis and systemic diseases, are topics worthy of attention.